Draft Annual Plan 1995-96 Part II Government of Maharashtra - Planning Commission (Planning Commission, 1995)
Agricultural and Allied Services, Rural Development, Irrigation and Flood Control, Industry and Minerals, Transport, Science, Technology and Environment, Social Services, General Services, Special Area Programme.
Government of Maharashtra, Planning Department